Opposition in Times of COVID-19: To Support or Not to Support? - Vande Walle, Britt; Wolfs, Wouter; Van Hecke, Steven (Politics of the Low Countries, 2025)
COVID-19 has hit many countries all over the world, and its impact on (party) pol‐ itics has been undeniable. This crisis situation functions as an opportunity struc‐ ture incentivising opposition forces to support the government. Not much is known about what drives opposition parties to (not) support the government in crisis sit‐ uations. This article integrates the literature on rally-around-the-flag, political opportunity structures, party types and party goals. More specifically, we focus on the behaviour of opposition parties towards the government’s crisis response to the COVID-19 pandemic. We analyse whether and how the party type influences the position of the party vis-à-vis the governmental coalition, focusing on the case of Belgium. We categorise the seven opposition parties in Belgium as challenger or mainstream parties and explain their behaviour on the basis of policy-, office- or vote-seeking motives. Our analysis is based on party voting behaviour, elite inter‐ views and an analysis of the main plenary debates.